Physical and Chemical Characterizations of Novel Bioactive Caries Detecting Solution - Shashirekha Govind; Sushant Kumar Kamilla; Binita Nanda; Amit Jena; Neeta Mohanty (Wolters Kluwer Medknow Publications, 2021)
Introduction: The nature and progression of acute and chronic carious lesion are extremely variable on different tooth surfaces. Early detection of dental caries is challenging for clinicians and involves careful visual and tactile examination. Caries detection dyes and chemomechanical caries removal solutions guide the clinicians in the removal of infected dentin. This study aims to prepare and analyze the physical, chemical, and thermal characterizations of novel bioactive caries detecting dye solution (BCD) and its effectiveness in caries removal from the tooth structure. Materials and Methods: BCD is a combination of contrast agent (iobitridol), chitosan (CS), nanohydroxyapatite (nHAP), and coloring agent. It is synthesized, lyophilized, and subjected to Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), and differential scanning calorimeter (DSC) analysis. Pilot study was conducted by applying BCD on two extracted carious teeth for evaluating caries removal efficiency under a microscope (10x). Scanning electron microscopy (SEM) image analysis was done to assess the percentage of dentinal tubules occlusion. Results: FTIR, XRD, and DSC analysis revealed that BCD has compatible interfacial bond between the components and is endothermic. Effective caries removal was seen under a microscope and SEM analysis revealed mean 77.66% of dentinal tubules occlusion. Conclusion: BCD is a stable solution without exothermic reaction, has caries identifying potential, and helps in caries removal. BCD is also bioactive in nature due to the presence of CS and nHAP as ingredients.